Athletes` perceptions of coaching competency and team conflict in sport teams: A multilevel analysis - González-Ponce, I.; Leo, F. M.; Jiménez, R.; Sánchez-Oliva, D.; Sarmento, H.; Figueiredo, A.; Garcia-Calvo, T. (European Journal of Sport Science, 2018)
The purpose of this study was to examine the relationship between coaching competency and team conflict, at individual and team levels, over the season. The participants were professional female and male soccer players, who participated in the First and Second Division. A longitudinal study was performed. At Time 1, the sample of participants consisted of 581 soccer players aged between 15 and 39 years. At Time 2, 549 players were recruited from the original sample aged between 15 and 37 years. Finally, at Time 3, the sample comprised 576 players aged between 15 and 37 years. All participants completed a multi-section questionnaire assessing coaching competency (motivation, game strategy, technique competency, and character-building competency) and team conflict (task conflict and relationship conflict). Results showed that both task and relationship conflict increased significantly over time. Multilevel modelling analysis showed that game strategy and character-building competencies negatively predicted both task and relationship conflicts at the individual level, whereas motivation competency was also added as a significant predictor of task conflict at the team level. Moreover, technique competency positively predicted task conflict at the team level. The current study suggests the importance of coaching competency in group dynamics in sport.